Գրիչ և մանրանկարիչ Մխիթար Անեցու կյանքն ու ձեռագրական ժառանգությունը - Մինասյան, Թամարա
At the beginning of the 14th century, as a result of the political and economic situation in the former Bagratid capital of Ani, many inhabitants left their native city and settled in Cilicia, Crimea, Van, Trebizond, and Poland, as well as in a number of settlements in Persia, including Soltaniyeh, the capital of the Mongol Ilkhanate. Mkhit‘ar Anets‘i, a famous 14th century scribe, miniaturist and bookbinder, was also among those who emigrated to Soltaniyeh. The artist, who had begun his activity in Ani, continued it in Soltaniyeh, where he acquired a great reputation. Four manuscripts produced by Mkhit‘ar Anets‘i have come down to us: all are copied on paper, written in beautiful, well-proportioned minuscule (bolorgir) and tastefully illustrated. The manuscripts date from 1321 to 1357. Three of them are housed in the Mashtots Matenadaran (Mss M2961, M4429, and M7740) and one manuscript is housed in the manuscript library of the Armenian Patriarchate in Jerusalem (Ms J1941). Mkhit‘ar is the scribe, illuminator and binder of two of the manuscripts, and he copied the other two in collaboration with miniaturist Avag, a pupil of the Gladzor school who later settled in Soltaniyeh. Educated in the cultural circles of Ani, Mkhit‘ar carried with him the traditions of the Ani school and became one of the most prominent representatives not only of the Soltaniyeh scriptorium but of Armenian cultural life in general. With the collapse of the Ilkhanate in 1385, Soltaniyeh lost its status as capital and, as a result of Tamerlane’s invasions, the population moved to safer locations, notably Tabriz. The activity of the Armenian scriptorium of Soltaniyeh, whose last scribe was Mkhitar Anets‘i, also came to an end, thus closing the fruitful period of activity of this writing centre which lasted for about thirty years. В начале XIV века, из-за неблагоприятной политической и экономической ситуации в столице Ани многие его жители покинули родной город и поселились в Киликии, Крыму, Ване, Трапезунде, Польше, в ряде населенных пунктов Персии, в том числе в Султании, столице Ильханата. Среди тех, кто эмигрировал в Султанию, был и Мхитар Анеци, знаменитый писец, миниатюрист и переплетчик XIV века. В Султании он приобрел большую известность. До нас дошли четыре рукописи, созданные Мхитаром Анеци: все они написаны на бумаге красивым, хорошо калиброванным минускулом (болоргир – арм. букв. «округлое письмо») и богато иллюстрированы. Рукописи датируются 1321-1357 годами. Три из них хранятся в Матенадаране имени Месропа Маштоца (№№ 2961, 4429, 7740), одна – в хранилище Армянского патриархата в Иерусалиме (№ 1941). Мхитар был переписчиком, иллюстратором и переплетчиком двух из этих рукописей, а две другие он переписал в сотрудничестве с миниатюристом Авагом, выучеником школы Гладзор, который позже поселился в Султании. Сформировавшийся в культуре Ани, Мхитар привнес сюда традиции анийской школы и стал одним из самых ярких представителей не только султанийского скриптория, но и местной армянской культурной жизни в целом. С распадом Ильханата в 1385 году Султания перестала быть столицей, а из-за нашествия Тамерлана население перебралось в более безопасные места – в частности, в Табриз. Закончилась и деятельность армянского скриптория Султании, последним писцом которого был Мхитар Анеци, завершивший самый плодотворный, длившийся около тридцати лет, период его деятельности.
Keywords: Ձեռագրական մշակույթ